Syndrome Serotonin - Warni, Asri Indahning; Yulistiani, Yulistiani (Eduvest - Journal of Universal Studies, 2025)
Major depressive disorder (MDD) and generalized anxiety disorder (GAD) are prevalent mental health conditions often treated with antidepressants, including SSRIs, SNRIs, tricyclic antidepressants, and benzodiazepines. However, abrupt discontinuation or rapid dose reduction of these medications can lead to withdrawal syndromes, ranging from somatic symptoms like dizziness and nausea to psychological effects such as mood swings and suicidal thoughts. This study examines withdrawal events associated with various antidepressants, emphasizing the need for effective health management strategies. The research aims to review withdrawal symptoms across antidepressant classes, identify high-risk medications, and explore alternative tapering methods such as hyperbolic dose reduction. A systematic literature review analyzed clinical studies, case reports, and patient surveys to evaluate withdrawal prevalence, symptom severity, and duration. Findings indicate that short half-life antidepressants (e.g., paroxetine, venlafaxine) pose elevated withdrawal risks, with symptoms persisting from weeks to years. Hyperbolic tapering demonstrated reduced severity in cases like escitalopram withdrawal. Persistent post-withdrawal disorders, including post-SSRI sexual dysfunction (PSSD), were documented. The research underscores the importance of structured discontinuation protocols and clinician awareness in mitigating withdrawal effects within healthcare systems. Implications highlight the necessity for evidence-based clinical guidelines on antidepressant tapering and enhanced patient education initiatives to prevent non-compliance and abrupt cessation. Future research should investigate long-term outcomes of withdrawal management strategies in diverse care settings.